Learning outcome-based education through the application of project-based learning methods in teaching American life and institutions courses to produce creative and collaborative skills - Rizal, Sarif Syamsu; Triwibowo, Febri Dhany (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2025)
This article is based on the Indonesian government's policy regarding learning outcome-based education in higher education curricula. This research urgently needs to apply the project-based learning method to the American Society course, one of the cultural course groups in the English Study Programme, Faculty of Humanities, Universitas Dian Nuswantoro. The purpose of this study is to prove that the results of the learning process of Project Based Learning method are to improve the ability of students in project problem solving, to gain new knowledge and skills students in learning, to make students more active in solving complex project problems with results in the form of real products, to develop and improve students' creative skills in managing tools and materials to complete tasks or projects and to enhance collaboration between students, especially in group activities. The research outputs are (1) the arrangement of the planning, implementation, and evaluation of Project-based to American Life and Institutions course learning, and (2) the tangible products from the course learning project.